Creating an Education Game Using Wordwall: An Interactive Learning Media for English Language Teaching (ELT) - Fitria, Tira Nur (Teacher Training and Education Faculty of Syekh-Yusuf Islamic University Tangerang, 2023)
Wordwall is a web-based educational game to create fun quiz-based games. This research describes the creation of an educational game (quiz) by using Wordwall as an interactive learning media for English Language Teaching (ELT). This research is descriptive qualitative research. The analysis shows that creating/making an interactive English quiz with Wordwall is easy. We type in the browser and click https://Wordwall.net. Look in the upper right corner, if we have an account, click Log In, while if we do not have an account, click Sign Up. Fill in the requested personal data, namely Email address, password, confirm password, and location/country. We tick â€œI accept the terms of use and privacy policyâ€. Click Create Our First Activity Now. There are 18 available templates for free. Select one of the Quiz templates. Fill in the title of the activity/quiz and start filling in the questions and answers. Add an image by clicking on the image icon. Wordwall provides the images we need. Add a question for adding the next question. We can add up to 100 questions. We can choose the theme, font, and time and we can also change the quiz template. Click share to share the quiz with students.